TQM and HRM: An Integrated Approach to Organizational Success - Sharma, Bina; Rahim, M. A. (Journal of Comparative International Management)

(untitled) (Management Futures, 2021)
In the past, most managers considered total quality management (TQM) philosophy very different from human resource management (HRM) philosophy because TQM focused on incremental improvements from the bottom up, whereas the HRM functions were based on a top-down approach in the organization’s hierarchy. Their understanding of the word “TQM” not only depended on process management but also on managing the process itself as in statistical process control (SPC). Therefore, the very few managers who did pay attention to quality implemented it on the floor-level of HRM activities where the core functions of the organizations were performed. The emerging thinking of HRM, however, is that TQM complements HRM functions and provides long-term competitive advantages to organizations. Supporting these ideas, this paper reflects on the past, examines the present, and proposes an integrated framework for organizations’ overall success.